Industrial training: Secretary General II Office in Ministry of Education Malaysia / Muhammad Akif Airulanuar - Muhammad Akif, Airulanuar (Bachelor of Info. SC. (HONS) Records Management, 2015)
In this paper, I have been training for long period at the secretary general Il office in Ministry of education Malaysia and all the activities and project I have compile on this report. This report basically is about how students apply the knowledge of records management courses on the particular organization. I also have gain many experience on working environment and how to communicate with other people especially on perform a task and solve a problem. All the activities, experience, knowledge, and application are been compiled and this reports.